(untitled) (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY: In HIV-infected patients, comprehension of medication instructions is an essential condition for adherence to Highly Active Antiretroviral Therapy (HAART). In this study, we used a self-reported questionnaire to know which sources of medication information HIV-infected patients used and their impact on adherence. In secondary objectives, we determined profiles of non-adherent patients and specified the role of the pharmacist. METHODS: A cross-sectional, observational study was conducted in one community pharmacy and one French university hospital pharmacy, in HAART-naïve or not patients, from April to June 2009. RESULTS: During the 3-month study period, 233 HIV-infected patients were included. The majority of patients sought information about their HAART treatments from the hospital physician (79.8%), the community physician (74.2%), and patient information leaflets (73.8%). The community and hospital pharmacists were consulted by respectively 16.3% and 3.4% of patients. According to multivariate regression analysis, adherence seemed to be associated with the sources of information “community physician”, “hospital physician”, “internet”, and the potential support of patient associations. A total of 65.7% of patients were considered to be adherent. CONCLUSIONS: In our study, among sources used by HIV-infected outpatients, their physicians are the most helpful sources of information about HAART. Regarding practice implications, the key role of the pharmacist is underutilised, indicating the need for improved communication between the pharmacist and outpatients.